A Descriptive Study of Knowledge, Attitude, and Awareness of Basic Life Support Among the Students of the Faculty of Veterinary Medicine - Jasa, Zafrullah Khany; Putra, Teuku Romi Imansyah; Al-Mathari, Alif; Farhana, Rika; Zulkifli, Baidillah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
Basic life support (BLS) is a first-aid measure performed to restore vital organ functions in cardiac or respiratory arrest patients. This research was conducted on the students of the Veterinary Medicine Faculty in the 2018th and 2019th entry years from November 15th 30th, 2021. This study was a descriptive observational study using a cross-sectional research design. Two hundred two respondents in this study were selected by stratified random sampling. Data from respondents were collected using an online questionnaire via Google Forms. The results of this study indicated that most respondents were 20 years old (46.5%), female (65.8%), and the number of respondents from each generation was the same. The data analysis of the respondents' basic life support showed that they possessed a minimal level of knowledge (60.9%), good attitude (66.8%), and good awareness (56.9%). According to these findings, most students had positive attitudes and awareness of basic life support. The aspect of knowledge about basic life support practices among these students falls into the poor category; therefore, there is a need to step up the socialization and training process.